If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 11x = -58 + x Solving 2 + 11x = -58 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2 + 11x + -1x = -58 + x + -1x Combine like terms: 11x + -1x = 10x 2 + 10x = -58 + x + -1x Combine like terms: x + -1x = 0 2 + 10x = -58 + 0 2 + 10x = -58 Add '-2' to each side of the equation. 2 + -2 + 10x = -58 + -2 Combine like terms: 2 + -2 = 0 0 + 10x = -58 + -2 10x = -58 + -2 Combine like terms: -58 + -2 = -60 10x = -60 Divide each side by '10'. x = -6 Simplifying x = -6
| (e+1)*4=20 | | 15700+26883-3579= | | 2r^2-2r-1= | | 7-6+15x+9x=49 | | n^2-22+120=0 | | -2s+3=-5s+24 | | 3+x-5=4+2(x-1) | | 6x+14+9=41 | | 4*cos*2*x=1 | | (-5x)(-6y)(2z)= | | x=2700+.1x | | 5+x=2x-(-3) | | 7+30x=20x+13 | | 2x-16x^(-1/2)=0 | | 2x-16x^-1/2=0 | | 30-5x=12-7x | | (x+1)(2x^2-9x-4)=0 | | 4x+7=-17-2x | | y=2x-3x+2y+14 | | [5y+(5x+4)][5y-(5x+4)]=0 | | 70x+10-54x-6=45x+45 | | 5(2x+1)=x+30 | | 48+9x=-3 | | X+15y=155 | | 0=3x^2-9x-27 | | 2x^2+mx+3m=0 | | 2-x-x^3=3x-2 | | Y=3x^2-9x-27 | | -16/d=-4 | | 3a-9ab-5-4ab+2a= | | 12+x=-24(6-x) | | 2x^2+4x-87=0 |